2012
DOI: 10.1039/c1dt11340b
|View full text |Cite
|
Sign up to set email alerts
|

Further studies of fluoride ion entrapment in octasilsesquioxane cages; X-ray crystal structure studies and factors that affect their formation

Abstract: A range of fluoride-encapsulated octasilsesquioxane cage compounds have been prepared using the TBAF route. Our studies suggest that whilst it is relatively straightforward to prepare fluoride-encapsulated octasilsesquioxane cage compounds with adjacent sp(2) carbons, leading to a range of aryl and vinyl substituted compounds, the corresponding sp(3) carbon derivatives are more capricious, requiring an electron withdrawing group that can stabilize the cage whilst not acting as a leaving group. Analysis by X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
(62 reference statements)
3
49
0
Order By: Relevance
“…Our initial curiosity was for X‐ray structures showing noncovalent contacts between anions and tetrel atoms, where the usual nucleophilic attack with the concomitant valence expansion of the tetrel atom did not occur. For us, one of the most fascinating families of compounds was reported by P. G. Taylor et al . (two examples are shown in Figure ), where they showed that the utilization of n ‐butylammonium fluoride improved the synthesis of spherosilicates.…”
Section: Inspiring Structuresmentioning
confidence: 98%
“…Our initial curiosity was for X‐ray structures showing noncovalent contacts between anions and tetrel atoms, where the usual nucleophilic attack with the concomitant valence expansion of the tetrel atom did not occur. For us, one of the most fascinating families of compounds was reported by P. G. Taylor et al . (two examples are shown in Figure ), where they showed that the utilization of n ‐butylammonium fluoride improved the synthesis of spherosilicates.…”
Section: Inspiring Structuresmentioning
confidence: 98%
“…In the a-type binary system, the OH···N HB interaction is characterized by a Lp N !σ*(OÀ H) orbital interaction, where LpN represents the lone-pair orbital on the N atom and σ*(OÀ H) denotes the anti-bonding orbital of the OÀ H bond. This quantity in Table S2 varies from 15 kJ/mol for the weak HBs involving NCH up to more than 50 kJ/mol for NH 3 and IM. However, in the trimers involving the two latter bases, E (2) derives instead from a Lp O !σ*(NÀ H) transfer which signals the proton transfer from O to N. In addition, no linear relationship is found between the binding energy and the second-order perturbation energy in the a-type dimer.…”
Section: Effects Of Adding Mgclmentioning
confidence: 99%
“…Noncovalent interactions play an important role in supramolecular chemistry, [1] molecular recognition [2] and crystal engineering. [3,4] Most of these interactions can also be called σhole interactions according to their origin. The concept of "σhole", a region of positive molecular electrostatic potential (MEP) on the outermost portion of an atomic surface, was proposed by Politzer et al [5] However, a negative or even neutral σ-hole was also suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Taylor et al [8] reported that the synthesis of spherosilicates is significantly improved using n-butylammonium fluoride (TBAF) as a catalyst. Interestingly, during the reaction work-up a new class of cage compound was obtained showing a fluoride ion perfectly centered within the octasilsesquioxane cage (see Figure 1).…”
mentioning
confidence: 99%
“…RI-MP2/aug-cc-pVDZ F À @Tr 8 O 12 (OH)8 optimized complexes and the equivalent X-ray structures. Distances in .…”
mentioning
confidence: 99%